1991
DOI: 10.1001/archsurg.1991.01410260101014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intestinal Permeability in Endotoxic Pigs

Abstract: Infusing pigs with lipopolysaccharide (LPS) decreases superior mesenteric artery blood flow (Qsma), suggesting that mesenteric hypoperfusion may be responsible for LPS-induced alterations in gut mucosal permeability. To test this hypothesis, we studied four groups of anesthetized swine. Group 1 animals (N = 6) were infused with LPS (250 micrograms/kg over 1 hour beginning at 60 minutes) and continuously resuscitated with Ringer's lactate (48 mL/kg per hour). In group 2 (N = 5), Qsma was decreased by 50% by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…However, some animal studies provided negative evidence (21,22), e.g. uptake of amino acids by everted gut sacs prepared from septic animals was significantly reduced (21).…”
Section: Effects Of Lps Treatment On the Dynamics Of Plasma Free Bcaamentioning
confidence: 99%
“…However, some animal studies provided negative evidence (21,22), e.g. uptake of amino acids by everted gut sacs prepared from septic animals was significantly reduced (21).…”
Section: Effects Of Lps Treatment On the Dynamics Of Plasma Free Bcaamentioning
confidence: 99%
“…81 Hypoperfusion per se contributes, but is not indepedently sufficient to account for all mesenteric permeability mechanisms. 82 However, hypoperfusion as well as pro-inflammatory cytokines are triggers for epithelial cellular apoptosis, all of which are putative incriminating agents/events in sepsis-induced gut hyperpermeability. Intestinal epithelial apoptosis in human sepsis 83 can in fact compromise mucosal integrity whereas Bcl-2 intestinal overexpression is partially protective in mice challenged with Pseudomonas aeruginosa pneumonia.…”
Section: The Intestine In Sepsismentioning
confidence: 99%
“…Infections develop in as many as one-third of all patients admitted to surgical intensive care units and are associated with increased mortality and a significant prolongation of intensive care unit stays [18]. Although the pathophysiology of sepsis, septic shock, and multiple organ failure remains elusive, much evidence has been accumulated implicating increased vasopermeability with altered endothelial cell function in the pathologic process [19,20]. Early studies concentrated on the bacteria and their products or byproducts in the pathophysiology of sepsis, but more recent studies have indicated that the immunologic response, mounted in response to the inciting agent(s), may have a detrimental effect on normal homeostasis [5,21,22].…”
Section: Discussionmentioning
confidence: 99%